Analysis of the potential of Sendang Silowo in Mandirejo Village, Merakurak District, Tuban Regency as Aquatic Ecotourism - Andriani, Riska; Andayani, Hana Dwi (Journal of Natural Sciences and Learning, 2024)
Ecotourism is a tourism activity that places responsibility on preserving nature and is able to provide a positive economic impact and welfare to local communities. Ecotourism focuses on three things, namely sustainability of nature, providing economic benefits, and being accepted in the social and cultural life of society. Tuban Regency is one of the districts in East Java Province which is located on the north coast. Tuban Regency has aquatic ecotourism which attracts many tourists, for example Sendang Silowo Ecotourism which is in Mandirejo Village, Merakurak District. In this research, the research method used is a qualitative descriptive method, data collection uses field observation methods, interviews, and uses SWOT analysis which is presented in the form of a simple SWOT analysis table to find out how far along the development and management process of Sendang Silowo Ecotourism is. This analysis aims to maximize the potential that can be developed into sustainable aquatic ecotourism in accordance with ecotourism principles.